Preparation and characterization of cellulose laurate ester by catalyzed transesterification - Wen, Xiaoxiang; Wang, Huihui; Wei, Yi; Wang, Xiaoying; Liu, Chuanfu (Carbohydrate polymers, 2017)
•Cellulose laurate was prepared by a mild transesterification catalyzed with DBU.•The degree of substitution of cellulose laurate ranged from 1.47 to 2.74.•FT-IR and NMR analyses confirmed the attachment of side chains onto cellulose.•The thermal stability increased upon transesterification in AmimCl/DMSO system.•The increased hydrophobicity and ductility facilitate the application of cellulose. The preparation of cellulose laurate was investigated through transesterification in 1-allyl-3-methylimidazolium chloride (AmimCl)/dimethyl sulfoxide (DMSO) cosolvent system by using vinyl laurate as an acylation reagent and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as an effective catalyst. The effects of reaction temperature, reaction time and the molar ratio of vinyl laurate to anhydride glucose unit (AGU) were investigated. The degree of substitution (DS) ranged from 1.47 to 2.74 under the selected conditions and the reaction order of three hydroxyl groups was C-6>C-3>C-2. The chemical structure cellulose laurate were explored by Fourier transform infrared (FT-IR) spectroscopy, 1H-nuclear magnetic resonance (NMR), 13C NMR, heteronuclear single quantum correlation (HSQC) and X-ray diffraction (XRD) to confirm the occurrence of transesterification. The improved thermal stability of cellulose laurate was proved by the thermogravimetric analysis (TGA). The tensile analysis and the contact angle measurement confirmed the ductile behavior and the hydrophobicity of the films made from cellulose laurate.